Atmospheric degradation of 2-chloroethyl vinyl ether, allyl ether and allyl ethyl ether: Kinetics with OH radicals and UV photochemistry. (August 2017) - Antiñolo, M.; Ocaña, A.J.; Aranguren, J.P.; Lane, S.I.; Albaladejo, J.; Jiménez, E.
Abstract: Unsaturated ethers are oxygenated volatile organic compounds (OVOCs) emitted by anthropogenic sources. Potential removal processes in the troposphere are initiated by hydroxyl (OH) radicals and photochemistry. In this work, we report for the first time the rate coefficients of the gas-phase reaction with OH radicals ( k OH ) of 2-chloroethyl vinyl ether (2ClEVE), allyl ether (AE), and allyl ethyl ether (AEE) as a function of temperature in the 263–358 K range, measured by the pulsed laser photolysis–laser induced fluorescence technique. No pressure dependence of k OH was observed in the 50–500 Torr range in He as bath gas, while a slightly negative T -dependence was observed. The temperature dependent expressions for the rate coefficients determined in this work are: k OH, 2 ClEVE ( T ) = ( 9.0 ± 2.0 ) × 10 − 12 exp ( 478 ± 72 T ) c m 3 molecul e − 1 s − 1, k OH, AE ( T ) = ( 1.3 ± 0.4 ) × 10 − 11 exp ( 442 ± 91 T ) c m 3 molecul e − 1 s − 1, k OH, AEE ( T ) = ( 5.8 ± 1.3 ) × 10 − 12 exp ( 563 ± 62 T ) cm 3 molecule − 1 s − 1, The estimated atmospheric lifetimes (τOH ) assuming k OH at 288 K were 3, 2, and 4 h for 2ClEVE, AE and AEE, respectively. The kinetic results are discussed in terms of the chemical structure of the unsaturated ethers by comparison with similar compounds. We also report ultraviolet (UV) and infrared (IR) absorption cross sections (σλ and σ ( ν ˜ ), respectively). We estimate the photolysis rate coefficients in the solar UV actinic region to be less than 10 −7 s −1, implying that these compounds are not removed from the atmosphere by this process. In addition, from σ ( ν ˜ ) and τOH, the global warming potential of each unsaturated ether was calculated to be almost zero. A discussion on the atmospheric implications of the titled compounds is presented. Highlights: UV and IR absorption cross sections are reported for three unsaturated ethers. Rate coefficients of the OH-reaction of these unsaturated ethers are determined. A slightly negative activation energy is observed for k OH between 263 and 358 K. OH-reaction, with a few hours lifetime, occurs in a greater extent than photolysis. Negligible contribution of these species to the global warming.